rachitshahIt seems like the steps from the given explanation accomplish the following:
1)
Find the distance of the original diagonal: (6-0)^2 + (2-6)^2 = X^2; X = root 52
2)
Find the midpoint of the original diagonal: (6+0)/2, (6+2)/2 = (3,4)
3)
Find the equation for the line for the other diagonal, since this will be the line that has the coordinates closest to (0,0)
Key to this step: This line is the perpendicular bisector of the diagonal (
the diagonals of squares are perpendicular bisectors = fact in geometry)
You can find the equation for the line the other diagonal by doing the following:
a) y = mx + b (generic equation for line)
b) find the slope of the original diagonal: (6-2)/(0-6) = -2/3 and take the negative reciprocal of this = 3/2 since the other diagonal is perpendicular
c) now you have y = 3x/2 + b; find the value of b by plugging in (3,4) and you get y = 3x/2 - 1/2, which is the same thing as y-4 = 3/2(x-3)
4) Distance from farthest coordinates to midpoint of diagonal = Distance from shortest coordinates to midpoint of diagonal = 1/2 the length of the diagonal (in this case, (root52/2)^2).
5) The distance from the farthest or shortest coordinates of the diagonal to the midpoint can be solved by using pythagorean theorem:
(x-3)^2 +(y-4)^2 = (root52/2)^2. (root52/2)^2 = 13
6) From step 3 you know that y-4 = 3/2(x-3). Plug this into y for step 5 above ==> (x-3)^2 + (y-4)^2 = 13 --> (x-3)^2 + [3/2(x-3)]^2 = 13 -->
(x-3)^2 +9/4(x-3)^2 = 13; solving for x gives you (x-3)^2 = 4, so x can be 1 or 5.